Sorcery trials, cultural relativism and local hegemonies - Granjo, Paulo (2012)
This book addresses the important topic of access to justice and security in Mozambique – two areas which are of core concern to the majority of Mozambicans, and not least to those who are poor. Since the 16 year civil war ended in 1992, the state police and the judiciary have undergone comprehensive reform efforts as part of the country’s democratic transition. However, despite massive international investment in the formal state institutions, many challenges remain in terms of ordinary citizens’ access to justice and public safety. In fact, in most situations the majority of Mozambicans turn to customary and community-based institutions to have their disputes and crimes resolved, and in worse case scenarios they ‘take the law into their own hands’. Justice is frequently dispensed by traditional authorities, community courts, village secretaries, community policing actors, civil society organisations and traditional healers. At times they do so in collaboration with the state police and the courts, and at other times in competition with them. In fact, much of what goes on in practice is highly informal. This is also the case when the state police frequently resolve crimes in the ‘local way’ and when community court judges ignore formal legislation. These empirical dynamics of legal pluralism is the central topic of this edited volume. The book with its 13 chapters contains a richness of case studies on state and non-state mechanisms of justice and public safety across Mozambique, and with insights from Angola, Cape Verde, and Sierra Leone (by DIIS researcher Peter Albrecht). It links the empirical insights to wider theoretical and policy-related questions. The point of departure of the book is the official recognition of legal pluralism in the 2004 Constitution of the Republic of Mozambique, which makes Mozambique a rather unique case globally. The book contributes to a critical discussion of this constitutional commitment - and its practical and political implications - based on solid historical, sociological and anthropological research into the everyday dynamics of legal pluralism. The book also includes a general Introduction written by DIIS researcher Helene Maria Kyed and CESAB researcher, and former Supreme Court judge, João Carlos Trindade. They here provide an overview of justice and security providers in Mozambique as well as a number of policy recommendations for the government and its international development partners. This publication contributes to the DIIS justice and security theme and is produced in joint collaboration with the Mozambique-based research centre, Centro de Estudos Sociais de Arquino Bragança (CESAB). The book is available in both English and Portuguese. It is published with financial support from the Friedrich Ebert Stiftung.